Research of behavioural reactions when modelling the total ischemia of the brain - O. V. Martynova; L. A. Zhilinkova; V. V. Gureev; M. A. Martynov; E. A. Beskhmelnitsyna; D. A. Kostina; O. V. Anciferov; I. Y. Shkileva (Кубанский научный медицинский вестник, 2015)
Dependence of psychoneurological deficiency at rats from severity of injury of a brain, on four-vascular model of a total ischemia of a brain is investigated. Results of research prove a tendency of deterioration of the psychoneurological status of animals at increase in weight of ischemic injury of a brain that allows to judge on extent of violation of behavioural reactions weight of ischemic damage of a brain and its correction.